2020
DOI: 10.1111/jdv.16464
|View full text |Cite
|
Sign up to set email alerts
|

European S1 guidelines on the management of lichen planus: a cooperation of the European Dermatology Forum with the European Academy of Dermatology and Venereology

Abstract: Lichen planus (LP) is a chronic inflammatory and immune-mediated disease that affects the skin, hair, nails and mucous membranes. Although there is a broad clinical spectrum of lichen planus manifestations, the skin and oral cavity remain the major sites of involvement. A group of European dermatologists with a long-standing interest and expertise in lichen planus has sought to define therapeutic guidelines for the management of patients with LP. The clinical features, diagnosis and possible medications that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
172
0
37

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(212 citation statements)
references
References 144 publications
(127 reference statements)
3
172
0
37
Order By: Relevance
“…HPV16, HSV17), & changes in the mucosal microbioma (e.g. Candida species, various other bacteria) 1 Medical conditions such as auto immune disease, diabetes, chronic liver disease, intestinal diseases, increases cholesterol level, hypertension and infections can also cause onset of oral lichen planus 13. Systemic medicines can also contribute to the production of oral lichenoid reactions (OLR) and lichen planus, such as nonsteroidal antiinflammatory drugs, antihypertensives, and oral hypoglycemics. Amalgam, copper , and nickel from dental restorative content can also be related to the localization of OLR in some patients 14 The table below briefly describes some of the etiological features of oral lichen planus.…”
Section: Etiologymentioning
confidence: 99%
See 4 more Smart Citations
“…HPV16, HSV17), & changes in the mucosal microbioma (e.g. Candida species, various other bacteria) 1 Medical conditions such as auto immune disease, diabetes, chronic liver disease, intestinal diseases, increases cholesterol level, hypertension and infections can also cause onset of oral lichen planus 13. Systemic medicines can also contribute to the production of oral lichenoid reactions (OLR) and lichen planus, such as nonsteroidal antiinflammatory drugs, antihypertensives, and oral hypoglycemics. Amalgam, copper , and nickel from dental restorative content can also be related to the localization of OLR in some patients 14 The table below briefly describes some of the etiological features of oral lichen planus.…”
Section: Etiologymentioning
confidence: 99%
“…While various studies have shown that OLP is a widely recognized chronic inflammatory autoimmune responsedriven disorder, the precise pathogenesis remains unknown 1,5,6,[15][16][17][18] . Some researchers found that emotional stress, infection and hypersensitivity contribute to OLP onset 1,6,19 . There has also been reported genetic vulnerability by haplotypes, such as HLA -A3, -A5, -A28, -B8, -B16, -Bw35, -B7, -B18, -Aw19, -Cw8 associated with different variants of LP 1 .…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations